Determinasi Kinerja Karyawan Vosco Group Setelah Melalui Pandemi Covid-19 - Tantia Eka Desti; Widiya Dewi Anjaningrum (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The relaxation of restrictions on community activities after the Covid-19 pandemic made Vosco Group owners optimistic about improving culinary business performance by optimizing employee performance. The purpose of this study was to determine the influence of work commitment, non-physical work environment, and work discipline on employee performance. Using a sampling technique in the form of saturated samples, as many as 37 respondents who are Vosco Group employees, both from Vosco Coffee Heritage, Vosco Coffee Malang, Kim Jong Yum Korean BBQ, and Fry N Shake by Vosco Coffee cafes, were studied using a Likert scale questionnaire. Quantitative data collected was analyzed using SEM-PLS analysis which was processed with SmartPLS-4.0.8.5 software. The results showed that both work commitment, non-physical work environment, and work discipline have a strong effect on employee performance, where work commitment is the strongest factor among the other 2 factors. So it was suggested to the owner of the Vosco Group to prioritize strengthening work commitments, only after that increasing work discipline, and improving the non-physical work environment in an effort to improve employee performance. In this study, the level of employee performance has not been distinguished in each cafe, so it will be interesting to carry out further research to find a more appropriate way to partially improve employee performance in each cafe.